Clinical research challenges in the era of cardiovascular medical devices - Borowiec, Jan W. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
New therapeutic alternatives, such as innovative medical devices, are frequently the only treatment options left for patients when other efficient medical modalities are lacking or insufficient. Development of novel devices, which are safe and effective, requires understanding of complex premarket and postmarket provisions, including characteristics of clinical trials. Speeding up patient access to new technologies may imply the need to make choices in terms of extent and robustness of clinical evaluation without losing the patient safety perspective. In such situations, some challenges can readily arise due to existing methodological solutions and aspects of current legislation in the field. In this context, some challenges, occurring at various stages of the device lifecycle, will be presented in order to observe the changes and hopefully to contribute to better knowledge and improvements in the area.